(untitled) (Research, Society and Development, 2025)
Microgreens are considered a class of plant foods at a very young stage of development, characterized by their delicate texture and high phytochemical content. The aim of this study was to evaluate different light intensities in the production of arugula microgreens. The seeds were sown in trays containing Soil Max®. The treatments consisted of different light intensities from LED lamps composed of 70% red light-emitting diodes and 30% blue light. The trays were kept in a growth chamber at 25 ± 1 °C under a 16-hour photoperiod. The experimental design was completely randomized, with five replicates. Twenty days after germination, plant height, number of leaves, stem diameter, and fresh mass were evaluated. The data for the light intensity factor were subjected to regression analysis. A significant effect of light intensity on all variables was observed. The greatest height (8.94 cm) was estimated at an intensity of 65.77 µmol m⁻² s⁻¹. For the number of leaves, a quadratic fit was observed, with an intensity of 76.66 µmol m⁻² s⁻¹ responsible for the highest estimated average (3.44 leaves per plant). The largest neck diameter (1.11 mm) was obtained at a light intensity of 78 µmol m⁻² s⁻¹. Regarding fresh mass, a quadratic behavior was observed, with a maximum estimated value of 36.73 g at an intensity of 45.56 µmol m⁻² s⁻¹. Light intensity influences the growth and biomass production of arugula microgreens, promoting specific photomorphogenic responses depending on the light conditions evaluated.